2011
DOI: 10.1214/11-aoas468
|View full text |Cite
|
Sign up to set email alerts
|

Spatial modeling of the 3D morphology of hybrid polymer-ZnO solar cells, based on electron tomography data

Abstract: A spatial stochastic model is developed which describes the 3D nanomorphology of composite materials, being blends of two different (organic and inorganic) solid phases. Such materials are used, for example, in photoactive layers of hybrid polymer zinc oxide solar cells. The model is based on ideas from stochastic geometry and spatial statistics. Its parameters are fitted to image data gained by electron tomography (ET), where adaptive thresholding and stochastic segmentation have been used to represent morpho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…The locations of the spheres are the points and the corresponding radii the marks. This representation allows us to analyse and model the set B ′′′ using tools from point-process theory; see Stenzel et al (2011).…”
Section: Some Numerical Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The locations of the spheres are the points and the corresponding radii the marks. This representation allows us to analyse and model the set B ′′′ using tools from point-process theory; see Stenzel et al (2011).…”
Section: Some Numerical Resultsmentioning
confidence: 99%
“…Spatial stochastic models as considered in Stenzel et al (2011), which are based on the results derived in the present paper, can be used to identify morphologies with improved efficiency by generating virtual morphologies and investigating the transport processes of electrons and excitons, respectively.…”
Section: Correlation Of Nanomorphology and Functionality In Polymer Smentioning
confidence: 99%
See 2 more Smart Citations
“…Stenzel et al [461] used this method to first determine the statistical properties of a P3HT-Zinc Oxide (ZnO) blend from transmission electron microscope images and then use this information to generate equivalent morphologies. The equivalence of experimental and generated morphologies was then tested by simulating exciton dissociation efficiencies [461], as well as connectivity and mobility of the P3HT and ZnO phases [462], and good agreement was observed in all cases. Westhoff et al [463] demonstrated that parameterising the statistical properties of a range of polymer-fullerene blend with respect to a process variable (spin speed in this case) could accurately predict the morphology of a blend which was not used to train the stochastic model.…”
Section: Different Ways Of Defining Morphologymentioning
confidence: 99%